Plasticity of the Melanocortin System: Determinants and Possible Consequences on Food Intake - Nuzzaci, Danaé; Laderrière, Amélie; Lemoine, Aleth; Nédélec, Emmanuelle; Pénicaud, Luc; Rigault, Caroline; Benani, Alexandre (Frontiers in Endocrinology, 2015)
The melanocortin system is one of the most important neuronal pathways involved in the regulation of food intake and is probably the best characterized. Agouti-related peptide (AgRP) and proopiomelanocortin (POMC) expressing neurons located in the arcuate nucleus of the hypothalamus are key elements of this system. These two neuronal populations are sensitive to circulating molecules and receive many excitatory and inhibitory inputs from various brain areas. According to sensory and metabolic information they integrate, these neurons control different aspects of feeding behavior and orchestrate autonomic responses aimed at maintaining energy homeostasis. Interestingly, composition and abundance of pre-synaptic inputs onto arcuate AgRP and POMC neurons vary in the adult hypothalamus in response to changes in the metabolic state, a phenomenon that can be recapitulated by treatment with hormones such as leptin or ghrelin. As described in other neuroendrocrine systems, glia might be determinant to shift the synaptic configuration of AgRP and POMC neurons. Here, we discuss the physiological outcome of the synaptic plasticity of the melanocortin system, and more particularly its contribution to the control of energy balance. The discovery of this attribute has changed how we view obesity and related disorders, and opens new perspectives for their management.